Association between pre-existing Pulmonary Hypertension and COVID-19 related outcomes in inpatient and ambulatory care settings - Shilpa Vijayakumar; David W. Louis; Emily Corneau; Sebhat Erqou; Stephen W. Waldo; Mary E. Plomondon; Madhura Gokhale; Wasiq Sheikh; Phinnara Has; Saad Marwan; J. Dawn Abbott; Matthew Jankowich; et al. (PLoS ONE, 2025)
Background Afflicting up to 1% of population, pulmonary hypertension (PH) is commonly associated with cardiopulmonary and metabolic diseases, but the effect of COVID-19 in patients with pre-existing PH remains unclear. Methods We conducted a retrospective cohort study in patients who had undergone right-heart-catheterization within the VA Healthcare system and had a subsequent hospital admission with COVID-19 (inpatient cohort, n=1204) or had COVID-19 positivity but not admitted (outpatient cohort, n=6576). Inpatient findings were confirmed in a non-VA validation cohort (n=656) who had undergone echocardiography with subsequent admission. PH was defined invasively as mean pulmonary artery pressure (mPAP) >20 mmHg and non-invasively as estimated right ventricular systolic pressure (RVSP) >30 mmHg. In-hospital outcomes (inpatient cohort) and 1-year mortality (outpatient cohort) were assessed using multivariable logistic or Cox regression adjusting for confounders. Results Pre-existing PH was independently associated with greater in-hospital mortality (PH using mPAP: adjusted odds ratio [aOR] 1.60, 95%CI: 1.04–2.46; PH using RVSP: aOR 2.12, 95% CI 1.18–3.82). Among outpatients, those with COVID-19 had >8-fold higher 90-day and 2.8 fold higher 91–365 day adjusted hazard of mortality irrespective of PH status. Hazards of 90-day hospitalization were similarly driven by COVID-19. The findings were comparable for patient subgroup with normal pulmonary capillary wedge pressures. Conclusion Pre-existing PH is independently associated with higher in-hospital COVID-19 mortality. In outpatients, COVID-19 positivity was associated with increased mortality over 1 year irrespective of PH status, with highest risk within the first 90 days.